Benefícios topográficos do Crosslinking no Ceratocone - Ferraris, Amanda Liberatore (2021)
Keratoconus is a disease characterized by the progressive bulging and thinning of the cornea, resulting in loss of visual acuity and irregular astigmatism. The disease is the principal cause of corneal transplants in Brazil. Although there are no therapies available that offer a cure, there are treatments capable of preventing its progression. Crosslinking (CXL) is the most recent treatment in this area, that consists in a procedure that uses ultraviolet A (UVA) radiation and riboflavin. Our study involved a retrospective analysis of 280 eyes submitted for CXL treatment. Measurements were undertaken of corneal topography, topography astigmatism, and variables such as allergy, blepharitis, and contact lens use before CXL. We analyzed preoperative 1 (1-182 days), postoperative 2 (183-364 days), postoperative 3 (365-546 days) and postoperative 4 (547 days and beyond). The mean age that went through the procedure was 18,8 years ± 4,4 years. The analysis between groups over and under 18 years had no significant difference in stabilization of the disease. There was a ratio of two men for one woman that realized the procedure (p <0,0001). Males had higher values of Kmax in the preoperative period (p=0,0091), as well as greater stabilization in the postoperative 3 (p= 0,028). It was found that patients with allergies tended to be younger when CXL was performed (allergic: 18,2 years ± 4,16 vs. non-allergic 19,5 years ± 4,55; p = 0,0039). Blepharitis and use of contact lenses prior to CXL did not influence the outcome of the procedure. Although it was not statistic significant, topography astigmatism had a reduction specially in postoperative 3. Parameters K1, K2 and Kmax had a significant reduction in distinct moments of postoperative. Therefore, we concluded that Crosslinking is a procedure statistically effective and secure, reinforcing its role in stabilizing keratoconus.